2009
DOI: 10.1007/s00405-009-0975-y
|View full text |Cite
|
Sign up to set email alerts
|

Subjective audiological tests and transient evoked otoacoustic emissions in patients with rheumatoid arthritis: analysis of the factors affecting hearing levels

Abstract: We investigated hearing functions in patients with rheumatoid arthritis (RA) using audiological tests and transient evoked otoacoustic emissions (TEOAEs). The study group consisted of 20 adult patients with RA (7 males, 13 females); 20 adult healthy subjects without RA (7 males, 13 females) were recruited as controls. All patients were evaluated by pure tone audiometry, high frequency audiometry, tympanometry and TEOAEs. There were no statistical differences between the study and control groups with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
2
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 25 publications
3
51
2
9
Order By: Relevance
“…Hearing impairment may be due to several different etiologies for each of these disorders. It may be due to vasculitis, ossicular involvement, neuritis or ototoxicity of the drugs used for the treatment of rheumatologic diseases (18). Thus, hearing loss may be seen in conductive, sensorineural or in mixed pattern in secondary AIED (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hearing impairment may be due to several different etiologies for each of these disorders. It may be due to vasculitis, ossicular involvement, neuritis or ototoxicity of the drugs used for the treatment of rheumatologic diseases (18). Thus, hearing loss may be seen in conductive, sensorineural or in mixed pattern in secondary AIED (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hearing loss may be seen in conductive, sensorineural or in mixed pattern in secondary AIED (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20). Özcan et al suggested middle ear involvement for the reason of hearing loss in RA (18). Whereas, Kastanioudakis and colleagues have shown SNHL in RA.…”
Section: Discussionmentioning
confidence: 99%
“…[15], timpanometri ile değerlendirdikleri 68 RA'lı hastada , %56 oranında esneklik kaybı olduğu-nu bildirmişlerdir. Literatürde RA'lı hastalarda kontrollere göre anlamlı işitme kaybı olmadığını belirten çalışmalar [16,17] olmakla birlikte %60'ın üzerinde işitme kaybı olduğunu bildiren çalışmalar da mevcuttur [5]. Çeşitli çalışmalarda işitme kaybının 0 -%17,4 arasında iletim tipi işitme kaybı [10,13,15] olduğu, 0 -%48 arasında ise SN tipte işitme kaybı [13,18] olduğu rapor edilmiştir.…”
Section: Discussionunclassified
“…However, substantial efficacy of etanercept has not been confirmed for improvement of hearing in patients with immune mediated cochlovestibular disorders [23]. Vasodilatators and antioxidants were also proposed for treatment of hearing loss in RA [13]. Successful use of adalimumab was verified for RA with sensorineural hearing loss [24].…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic reflexes were with normal thresholds, but with occasional prolonged latency. Besides increased hearing threshold, patients with RA have higher air-bone gaps, and increased wave I latency on ABRs [12,13].…”
Section: Discussionmentioning
confidence: 99%